Long and short-term pedogenetic processes in ferralsols from magmatic province of Paraná, Brazil - Chiapini, Mariane (2021)
Despite being widely studied, several questions are still without consistent answers, with respect to the genesis and morphology of ferralsols. The excessive focus of pedological investigations within the control section (200 cm) has systematically left aside the records that may exist of different moments in the pedogenesis of these soils and that are registered at greater depths. The objective of this work is to understand the main pedogenetic processes that act in complete profiles of ferralsols of the Paraná Magmatic Province (PMP), and how the Quaternary climatic changes may have influenced them, since the processes have different temporal scale, long and short-term. Ten soil profiles were described and collected in a topo-climate-sequence in PMP (Guarapuava: G1G4; Cascavel: C1C3 e Palotina: P1P3) under basaltic and rhyo-dacitic rocks. To this end, a combination of physical, chemical, mineralogical, geochemical and micromorphological analyses of soils in combination with the qualitative characterization of soil organic matter (SOM) and isotopic analyses of C and N for paleoenvironmental reconstruction was carried out. The ferralsols of PMP have developed in situ, responding to climatic and landscape changes according to a morphoclimatic process and intense geochemical weathering. In this context, a partial ferralitization process took place resulting in a predominance of kaolinite (3768%), with variable contents of gibbsite (3 28%), hematite (728%), goethite (113%) and traces of hydroxy-interlayered 2:1 minerals. Paleo and current environmental conditions affect the formation and stability of Fe oxides, giving rise to different moments and positions in the profiles of the rubification and brunification processes, characterizing the brownish and reddish colours. Pedorelict features such as iron nodules and dense clayey nodules were described and interpreted in a hierarchical relationship as developed in situ. Iron nodules originate in redoximorphic conditions in the weathering front in wetter periods and then decompose. The geric property appeared in these kaolinitic soils with gibbsite contents below 28%. The eutric property was identified in the Palotina profiles and it was hypothesized to be due to partial ferralitization followed by cycling of Ca and Mg carried out by a higher concentration of C4 plant roots under a drier and prolonged climate, combined with protection of microaggregates. There are different zones of intense bioturbation, even below the biomantle, influenced by the Quaternary climatic conditions. Different specific biofeatures allowed to identify the main bioturbation agents, some of them little or not registered in the literature in great depths. The genesis of microaggregates is complex, in saprolite there are microaggregates of geochemical, zoogenetic and physical origin, which are reworked by soil fauna to different soil depths. Complex microaggregates from the aggregation of smaller microaggregates and ant activity are also present in PMP ferralsols. The SOM and its isotopic composition were influenced by the Quaternary climatic conditions, recording the driest periods with a predominance of C4 plants, and higher contributions (%) of compounds affected by fire, allowing ferralsols to be used as paleoenvironmental records up to the most deep horizons.